Feasibility of free-breathing, GRAPPA-based, real-time cardiac cine assessment of left-ventricular function in cardiovascular patients at 3T - Zhu, Xiaomei; Schwab, Felix; Marcus, Roy; Hetterich, Holger; Theisen, Daniel; Kramer, Harald; Notohamiprodjo, Mike; Schlett, Christopher L.; Nikolaou, Konstantin; Reiser, Maximilian F.; Bamberg, Fabian (European journal of radiology, 2015)
Objectives - To determine the feasibility of free-breathing, GRAPPA-based, real-time (RT) cine 3T cardiac magnetic resonance imaging (MRI) with high acceleration factors for the assessment of left-ventricular function in a cohort of patients as compared to conventional segmented cine imaging. - Materials and methods - In this prospective cohort study, subjects with various cardiac conditions underwent MRI involving two RT cine sequences (high resolution and low resolution) and standard segmented cine imaging. Standard qualitative and quantitative parameters of left-ventricular function were quantified. - Results - Among 25 subjects, 24 were included in the analysis (mean age: 50.5±21 years, 67% male, 25% with cardiomyopathy). RT cine derived quantitative parameters of volumes and left ventricular mass were strongly correlated with segmented cine imaging (intraclass correlation coefficient [ICC]: >0.72 for both RT cines) but correlation for peak ejection and filling rates were moderate to poor for both RT cines (ICC<0.40). Similarly, RT cines significantly underestimated peak ejection and filling rates (>103.2±178ml/s). Among patient-related factors, heart rate was strongly predictive for deviation of measurements (p<0.05). - Conclusions - RT cine MRI at 3T is feasible for qualitative and quantitative assessment of left ventricular function for low and high-resolution sequences but results in significant underestimation of systolic function, peak ejection and filling rates.